2009
DOI: 10.1111/j.1440-1819.2009.01944.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin, sexually dimorphic features of the social brain, and autism

Abstract: The common features of autism spectrum disorder, a highly heritable representative pervasive developmental disorder with significant heterogeneity and multiple‐genetic factors, are severe dysfunction in social reciprocity, abnormalities in social brain regions, and disproportionately low probability in the female gender. Concomitantly, certain domains of mental function, such as emotional memory and social reciprocity, show a significant sex difference. In addition, recent neuroimaging studies have shown signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 106 publications
(160 reference statements)
2
49
1
Order By: Relevance
“…Peripheral or nasal administration of OT facilitates social recognition and trust in healthy humans (Guastella et al, 2008a andDitzen et al, 2009) and increases eye contact and recognition in autistic subjects (Hollander et al, 2007;Yamasue et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Peripheral or nasal administration of OT facilitates social recognition and trust in healthy humans (Guastella et al, 2008a andDitzen et al, 2009) and increases eye contact and recognition in autistic subjects (Hollander et al, 2007;Yamasue et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Apart from regulating lactation and uterine contraction, oxytocin acts as a neuromodulator in the central nervous system [219,220]. Both animal experiments and clinical research have confirmed the role oxytocin plays in social and repetitive behaviors [221].…”
Section: Human Oxytocin Receptor Gene (Oxtr)mentioning
confidence: 89%
“…8,9,[32][33][34][35][36][37][38][39][40] It has been reported that plasma OXT levels in autistic children are lower than those in age-matched normal controls, although the precise deviation is very small. 32,40) Infusion or nasal administration of OXT reduces repetitive behaviors or social interaction in adults with Asperger's disorders or autism.…”
Section: Implications For Developmental Disor-dersmentioning
confidence: 99%